The Effect of Financial Ratios on Stock Prices with Exchange Rates as a Moderating Variable (Study of BUMN Companies in the Construction Services and Basic Industries Sector Listed on the Indonesia Stock Exchange in 2014-2018) - Ramdhan, Dadan (IJTB (International Journal of Technology And Business), 2019)
Abstract The purpose of this study was to examine the effect of Return on Equity (ROE), Earning Per Share (EPS) and Debt to Equity Ratio (DER) on stock prices with exchange rates as a moderating variable in construction sector companies and basic industries listed on the Indonesia Stock Exchange in period 2014-2018. This research is a quantitative study using multiple linear regression test, t test and coefficient of determination test. Previously, the classical panel data assumption test which included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. There are 8 BUMN construction and basic industry companies listed on the Indonesia Stock Exchange as research objects. The results of this study indicate that the Earning Per Share (EPS) of the company has a significant positive effect on the price of its shares. While the Debt to Equity Ratio (DER) and Return on Equity (ROE) of the company do not significantly influence the stock prices. The results of this study also showed that the exchange rate did not moderate the relationship between DER and stock prices in several observed companies.   Keywords: Earning Per Share (EPS), Debt to Equity Ratio (DER), Return on Equity (ROE), exchange rates, and Stock Price.